2022
DOI: 10.1007/s00405-022-07295-w
|View full text |Cite
|
Sign up to set email alerts
|

The effect of female hormone in otosclerosis. A comparative study and speculation about their effect on the ossicular chain based on the clinical results

Abstract: Purpose This study aimed at identifying gender differences in the hearing thresholds in a sample of patients with otosclerosis before and after surgery to understand the impact of female hormones on auditory thresholds. Methods This retrospective study analyzed 184 patients (123 women and 61 men) affected by otosclerosis. All the patients were affected by conductive hearing loss and treated by stapedoplasty. Auditory thresholds at the baseline (T0) and one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The reason for the fluctuating auditory symptoms in our patient is unclear, but it is possible that the external sound stimulus or pressure changes might have affected endolymphatic dynamics by allowing sound transmission through the round window membrane but precluding the spread of sound waves through the oval window due to the fixed footplate. Another possible reason for fluctuating auditory symptoms is a potential progression in the stapedial tendon ossification by an unnoticed infection, inflammation or hormonal change[ 13 ]. Once middle ear malformation is clinically suspected, it can be diagnosed by temporal bone CT and exploratory tympanotomy.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the fluctuating auditory symptoms in our patient is unclear, but it is possible that the external sound stimulus or pressure changes might have affected endolymphatic dynamics by allowing sound transmission through the round window membrane but precluding the spread of sound waves through the oval window due to the fixed footplate. Another possible reason for fluctuating auditory symptoms is a potential progression in the stapedial tendon ossification by an unnoticed infection, inflammation or hormonal change[ 13 ]. Once middle ear malformation is clinically suspected, it can be diagnosed by temporal bone CT and exploratory tympanotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to those observed in different malignancies, also in otosclerosis there is a protection induced by sexual hormones [ 26 ]. Despite this protection, many authors found out that females are affected twice as often as males [ 2 , 20 , 27 , 28 ]. In this study, women represented 77% of cases, with a 3.34:1 female to male ratio.…”
Section: Discussionmentioning
confidence: 99%